SELF-STIGMA IMPACT ON SOCIAL FUNCTIONING OF PATIENTS WITH CHRONIC SCHIZOPHRENIA - Amal Gamal Shehata; Enas Mahrous Abd El Aziz (Indian Journal of Psychiatric Nursing)
Schizophrenia as a chronic mental illness has been found to be one of the most stigmatizing conditions. The experience of schizophrenia is not limited to the symptoms of the illness itself but it is also accompanied by the reactions of social environment, and the stigma associated with this disorder. To assess self-stigma impact on social functioning of patients with chronic schizophrenia, descriptive correlative research design was adopted. This study was conducted at outpatient clinics in El Abbassia Hospital-for Mental Health. Convenient eighty patients with chronic schizophrenia were recruited from the outpatient clinics who attend for follow up. Inventory of stigmatizing experiences, social functioning scale, and assessment of severity of negative symptoms scales were used to collect data. Findings revealed that, there was a moderate to severe degree of self-stigma. There were statistically significant positive correlations between experiences of participant's self-stigma and both, severity of patient's negative symptoms and social functioning especially recreational activities.